The experiences and perspectives of participating in a nature integrative rehabilitation programme when suffering from post-concussion syndrome: responses, gains, and impact from using enriched nature environments as a rehabilitation setting and integrating nature as rehabilitation means - Ulrik Sidenius; Sus Sola Corazon; Dorthe Varning Poulsen; Lisbeth Jul Olsen; Natasha Kæreby (International Journal of Qualitative Studies on Health & Well-Being, 2025)
Purpose This study aims to understand the perspectives of individuals participating in a nature integrative rehabilitation (NIR) programme for post-concussion syndrome (PCS) in Denmark. The focus is on benefits, challenges, and impact of using enriched natural environments in rehabilitation. Methods A qualitative approach was employed, utilizing semi-structured interviews with 23 participants who completed a 10-week NIR programme in a therapy garden. Thematic analysis was conducted to identify key themes and patterns in participants’ experiences. Results Participants reported enhanced emotional and sensory engagement with natural environments, leading to decreased PCS symptoms. The structured nature integrative activities promoted present-moment awareness, relaxation, and physical activity, which were valued by the participants. The facilitators’ ability to adapt activities to individual needs was crucial to the perceived benefit of the programme. Group settings provided social support, reducing feelings of isolation. Conclusions NIR supports individuals with PCS by enhancing emotional well-being, reducing symptoms, and providing coping strategies. Alongside social support, the flexibility of the activities, allowing individuals to engage according to their symptoms and capabilities, is critical for rehabilitative outcomes. Future research should explore long-term effects and refine intervention protocols for implementation in the healthcare system to ensure the efficacy of NIR for people with PCS.